Insights into the swelling process and drug release mechanisms from cross-linked pectin/high amylose starch matrices - Fernanda M. Carbinatto; Ana Dóris de Castro; Raul C. Evangelista; Beatriz S.F. Cury (Asian Journal of Pharmaceutical Sciences, 2014)
Cross-linked pectin/high amylose mixtures were evaluated as a new excipient for matrix tablets formulations, since the mixing of polymers and cross-linking reaction represent rational tools to reach materials with modulated and specific properties that meet specific therapeutic needs. Objective: In this work the influence of polymer ratio and cross-linking process on the swelling and the mechanism driving the drug release from swellable matrix tablets prepared with this excipient was investigated. Methods: Cross-linked samples were characterized by their micromeritic properties (size and shape, density, angle of repose and flow rate) and liquid uptake ability. Matrix tablets were evaluated according their physical properties and the drug release rates and mechanisms were also investigated. Results: Cross-linked samples demonstrated size homogeneity and irregular shape, with liquid uptake ability insensible to pH. Cross-linking process of samples allowed the control of drug release rates and the drug release mechanism was influenced by both polymer ratio and cross-linking process. The drug release of samples with minor proportion of pectin was driven by an anomalous transport and the increase of the pectin proportion contributed to the erosion of the matrix. Conclusion: The cross-linked mixtures of high amylose and pectin showed a suitable excipient for slowing the drug release rates.